Pengaruh Environmental Performance Terhadap Economic Performance Dengan Environmental Disclosure Sebagai Variabel Intervening - Widodo, Ari; S, Yuli Chomsatu; W, Endang Masitoh (Universitas Nusantara PGRI Kediri, 2020)
Abstract The purpose of this study is to see empirical evidence of the effect of environmental performance, environmental disclosure and economic performance. Manufacturing companies listed on the Indonesia Stock Exchange were the population in this study and participated in the PROPER program during the 2017-2018 period, by determining the sample by purposive sampling, a sample of 62 was obtained. The results of Path Analysis testing show that the high low of a company's economic performance is not influenced by the company's environmental performance. The test results also show that the environmental disclosure is influenced by the company's economic performance, and the level of economic performance is not influenced by the company's economic disclosure. The calculation result using Sobel Test shows that the economic performance of a company is influenced by the environmental performance which is disclosed in the company's annual report